Might a Securities Transactions Tax Mitigate Excess Volatility? Some Evidence From the Literature - Markus Haberer (University of Konstanz, Center of Finance and Econometrics (CoFE), 2004)
International financial markets are said to be excessively volatile due to destabilizing speculation and excessive market volume. Transactions taxes might help. From studying the literature we conclude that there must be an optimal market liquidity, which minimizes excess volatility. There are two effects when imposing a transactions tax. Both reduce excess volatility in highly speculative markets when tax rates are small. The total tax effect then is unambiguous. However, in illiquid markets the tax might raise volatility.
urn:nbn:de:bsz:352-opus-17579
Keywords: H20; G15; G18; 330; International Financial Markets; Securities Transactions Tax; Excess Volatility; Börsenkurs; Volatilität; Börsenumsatzsteuer; Internationaler Finanzmarkt; Wertpapierspekulation; Theorie